2017
DOI: 10.1093/dote/dox001
|View full text |Cite
|
Sign up to set email alerts
|

Upper esophageal sphincter motility in gastroesophageal reflux disease in the light of the high-resolution manometry

Abstract: This study aims to evaluate the upper esophageal sphincter (UES) motility in patients with gastroesophageal reflux disease (GERD) as compared to healthy volunteers. We retrospectively studied the HRM tests of 44 patients (median age: 61 years, 54% females) under evaluation for GERD. The manometric UES parameters of these patients were compared to 40 healthy volunteers (median age: 27 years, 50% females). Almost half of the patients had a short and hypotonic UES. Patients with extraesophageal symptoms had a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Findings on UES motility were further supported by the efficacy of UES assist device in the patients with laryngeal symptoms . However, another retrospective study that included 22 esophageal symptom patients, 22 extraesophageal symptom patients, and 44 healthy controls have found that both esophageal symptom patients and extraesophageal symptom patients had lower UES basal pressure and shorter UES length than healthy controls . Whether UES motility impairment is unique to LPR still remains uncertain.…”
Section: Discussionmentioning
confidence: 96%
“…Findings on UES motility were further supported by the efficacy of UES assist device in the patients with laryngeal symptoms . However, another retrospective study that included 22 esophageal symptom patients, 22 extraesophageal symptom patients, and 44 healthy controls have found that both esophageal symptom patients and extraesophageal symptom patients had lower UES basal pressure and shorter UES length than healthy controls . Whether UES motility impairment is unique to LPR still remains uncertain.…”
Section: Discussionmentioning
confidence: 96%
“…Results from our study are consistent with the physiological profile of the UES linked to supra-esophageal symptoms in prior studies. Nadaleto et al 15 found a shorter UES length and greater percentage of UES hypotonicity on HRM in patients with extraesophageal symptoms versus typical GERD symptoms. In another elegant study, Babaei et al 16 studied UES responses measured on HRM to rapid saline injection and slow acid infusion in healthy controls, typical GERD patients, and those with supra-esophageal symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…13,14 HRM studies have demonstrated that a hypotonic UES and impaired UES reflexes are associated with supra-esophageal symptoms. 15,16 Thus, a reasonable hypothesis is that defective UES barrier function could be a cause of supraesophageal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A study evaluating UES motility in patients with GERD reported that almost half of the patients had a short and hypotonic UES, and in those with extraesophageal symptoms, the proportion of hypotonic UES was even higher. 16 In another study, abnormalities in UES function were found in one-third of the patients with gastroesophageal reflux, including patients with laryngopharyngeal reflux and patients with typical GERD. The most common alteration was abnormal UES basal pressure (median of 59.8 mm Hg) in patients with GERD (normal reference value 73.5 mm Hg).…”
Section: Review Of a Particular Subjectmentioning
confidence: 94%
“…Torrico et al 13 Increase pressure during reflux Kuribayashi et al 15 Increase pressure during reflux Bognár et al 19 Hypertensive sphincter Kim et al 29 Increase UES pressure during transient LES relaxation Babaei et al 32 No increase in pressure during slow infusion of liquid into esophageal body Nadaleto et al 16 Short and hypotonic sphincter Benjamin et al 17 Decreased pressure Passaretti et al 18 Decreased pressure in patients with pharyngeal reflux Mendell et al 21 Slower transit through the sphincter Cassiani et al 22 Slower transit through the sphincter Alkan et al 30 No alteration of cricopharyngeal EMG Bastian et al 39 Inability to belch Abbreviations: EMG, electromyography; LES, lower esophageal sphincter; UES, upper esophageal sphincter.…”
Section: Reference Ues Alterationmentioning
confidence: 99%